2016
DOI: 10.1016/j.vaccine.2016.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and beliefs related to seasonal influenza vaccine among pregnant women in Thailand

Abstract: Background In 2009, Thailand recommended pregnant women be prioritized for influenza vaccination. Vaccine uptake among Thai pregnant women is lower than other high-risk groups. Methods During December 2012-April 2013, we conducted a cross-sectional survey of a convenience sample of Thai pregnant women aged ≥15 years attending antenatal clinics at public hospitals in 8 of 77 provinces. A self-administered questionnaire covered knowledge, attitudes, and beliefs related to influenza vaccination using the Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
59
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 24 publications
13
59
4
2
Order By: Relevance
“…This value is almost identical to the 21.6% found in the United States among pregnant minority women [47]. By contrast, higher values have been observed in the already mentioned survey in Thailand with 42% of the women who reported being willing to receive the seasonal influenza vaccine [26], in the United States 82.8% said they would be immunized if recommended by their physician [23], and in Pakistan 87% were willing to accept the vaccine [24]. …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This value is almost identical to the 21.6% found in the United States among pregnant minority women [47]. By contrast, higher values have been observed in the already mentioned survey in Thailand with 42% of the women who reported being willing to receive the seasonal influenza vaccine [26], in the United States 82.8% said they would be immunized if recommended by their physician [23], and in Pakistan 87% were willing to accept the vaccine [24]. …”
Section: Discussionsupporting
confidence: 77%
“…Therefore, it is important to design and to implement interventions in order to increase the vaccination rate. The value observed in the present study is higher than those reported in other countries, since no women had received influenza vaccination in the already mentioned study in India [34], 3% in Turkey [36], 4% in Thailand [26], and it is almost identical to the 6% in Iran [37], 10.9% in Germany [38], and 16% in Canada [39]. Whereas, it is substantially below the levels observed in Australia with an uptake of 27% [20], in France of 39% [40], in Belgium of 42.8% [41], and in the United States with levels ranging from 35% [14] to 66.4% [42].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Physicians were more likely to recommend influenza vaccine routinely when they had more than three years of practice, had treated pregnant women for influenza, perceived influenza vaccine to be effective and were aware of Ministry of Public Health’s (MOPH) recommendation of influenza vaccination in pregnancy. Understanding factors associated with Thai physicians’ decisions to recommend influenza vaccine to pregnant women is critical because physician recommendation of influenza vaccine is a key factor in Thai pregnant women’s decision to get vaccinated during pregnancy [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Provider recommendation has been found to be one of the most effective motivators of vaccination among pregnant women [13,14], a phenomenon which is also seen amongst Thai pregnant women [15]. Surveys in the United States have found significant support for influenza vaccination in pregnancy among obstetricians [16, 17] as well as a high rate of routine recommendations for influenza vaccination by providers [18].…”
Section: Introductionmentioning
confidence: 99%